La reconnaissance des acquis expérientiels: étude de cas de la politique d’admission des adultes à l’Université Laval - Heon, Lucie; Clourtier, Renee; Belanger, Pierre W. (Canadian Journal of Higher Education, 1986)
Has the inclusion of experience as a criterion of admission for adult students raised significantly the chances of these students of being admitted? The authors analyse the new admission policy at Laval University (1980) and, from a sample of400 candidates' dossiers, its practice age and a fair amount of experience appear to be important factors opening the door of university. However, the effects of these factors are particularly enhanced if experience is close to academic or cognitive learning or combined with a CEGEP diploma and a grade higher than 65%. Thus, experience does not seem to be used as a basis of admission of its own, but mainly to corroborate academic ability already expressed by good grades.